2018
DOI: 10.1016/j.ijheh.2018.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation strategies to reduce the generation and transmission of airborne highly pathogenic avian influenza virus particles during processing of infected poultry

Abstract: Airborne transmission of H5N1 highly pathogenic avian influenza (HPAI) viruses has occurred among poultry and from poultry to humans during home or live-poultry market slaughter of infected poultry, and such transmission has been experimentally reproduced. In this study, we investigated simple, practical changes in the processing of H5N1 virus-infected chickens to reduce infectious airborne particles and their transmission. Our findings suggest that containing the birds during the killing and bleeding first st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Few of them reported using dedicated garments while tending to poultry, even though this measure was a main recommendation of previous educational campaigns. Similarly, only 10% of participants who reported slaughtering poultry (the riskiest behavior because of the aerosols generated [21]) used any personal protective equipment. Reviewing, revising, and updating health education and awareness campaigns based on scientific evidence might assist in decreasing the incidence of infection with AIVs in Egypt (21).…”
Section: Discussionmentioning
confidence: 99%
“…Few of them reported using dedicated garments while tending to poultry, even though this measure was a main recommendation of previous educational campaigns. Similarly, only 10% of participants who reported slaughtering poultry (the riskiest behavior because of the aerosols generated [21]) used any personal protective equipment. Reviewing, revising, and updating health education and awareness campaigns based on scientific evidence might assist in decreasing the incidence of infection with AIVs in Egypt (21).…”
Section: Discussionmentioning
confidence: 99%
“…HPAIV infected chickens and ducks, and exposure of chickens and ferrets within the same air space as the slaughter process resulted in airborne transmission and infection indicating a plausible method for transmission of AIV in LPMS to poultry and humans, respectively. 57,58 For reasons not immediately clear, these risk factors were not significant for H9N2 infection in our study.…”
Section: Discussionmentioning
confidence: 54%
“…Other studies have reported risk factors such as handling dead birds, butchering, area of farm, swimming or bathing in household ponds, having sick or dead poultry, age, vaccination of poultry, and exposure to ducks . In experimental studies, influenza virus has been recovered from air samples during slaughter of asymptomatic H5N1 HPAIV infected chickens and ducks, and exposure of chickens and ferrets within the same air space as the slaughter process resulted in airborne transmission and infection indicating a plausible method for transmission of AIV in LPMS to poultry and humans, respectively . For reasons not immediately clear, these risk factors were not significant for H9N2 infection in our study.…”
Section: Discussionmentioning
confidence: 98%
“…Second, we were unable to confirm the sources of the viruses, whether crows were infected by contact with poultry at LBMs or whether they were responsible for spread of viruses among poultry or between LBMs, or other sources. However, Zhou et al isolated AIVs at LBMs in China and Bertran et al have demonstrated that experimental processing of HPAI A(H5N1) virus‐infected chickens and ducks generated infectious droplets and aerosols . Overall, LBMs were reported to be highly contaminated with AIVs by multiple studies in Bangladesh and other countries .…”
Section: Resultsmentioning
confidence: 99%
“…Second, we were unable to confirm the sources of the viruses, and ducks generated infectious droplets and aerosols. 12,13 Overall, LBMs were reported to be highly contaminated with AIVs by multiple studies in Bangladesh and other countries. 14,15 Taken together, these studies suggest that the most likely source of the aerosolized AIVs in LBMs in Bangladesh is from slaughtering of infected poultry.…”
Section: Re Sults and Discussionmentioning
confidence: 99%